Ship stability for masters and mates - Derrett, D. R.; Barrass, C. B. (Elsevier Butterworth-Heinemann, 2006)
Understanding ship stability is critical for all maritime students or professionals who are studying for a deck or engineering certificate of competency, or seeking promotion to a higher rank within any branch of the merchant marine or Navy. The sixth edition of the now classic 'Ship Stability' provides a comprehensive introduction to all aspects of ship stability and ship strength, squat, interaction and trim, materials stresses and forces. * The market leading ship stability text, widely used at sea and on shore* New content inclues coverage of now-mandatory double-skin tankers and fast ferries * Meets STCW (Standards of Training, Certification & Watchkeeping) requirements and includes self-examination material: essential reading for professionals and students alike